Occupational contact allergy in bricklayers, tile setters etc.: current spectrum of sensitization and recent time trends - Geier, Johannes; Lessmann, Holger; Skudlik, Christoph; Ballmer-Weber, Barbara K.; Weisshaar, Elke; Uter, Wolfgang; Schnuch, Axel (Allergologie select, 2017)
Background: Occupational exposure of bricklayers, construction workers, tile setters etc. has changed during the last years. For some years now, all manually handled cement in the European Union and in Switzerland is chromate-reduced. Epoxy resin systems are being used in more and more fields of application. Improved worker’s protection, especially wearing protective gloves, is promoted. These changes influence the spectrum of occupational contact sensitization. Objective: Description of the current allergen spectrum in patients working in the building trade who suffer from occupational contact dermatitis. Material and methods: Retrospective analysis of data of the Information Network of Departments of Dermatology (IVDK), 2009 - 2011. Results: During the study period, 245 bricklayers, construction workers, tile setters etc. with occupational dermatitis have been patch tested. Potassium dichromate was the most frequent allergen, yielding 15.1% positive reactions, followed by epoxy resin with 13.7% positive reactions. Beyond that, there were 8 additional components of epoxy resin systems (5 reactive diluents and 3 amine hardeners), as well as 9 rubber ingredients, mainly thiurams, among the 30 most frequent allergens. In the course of time, a decline of chromate sensitization could be noted, paralleled by a decline of cobalt sensitization. In contrast, sensitization to epoxy resin has increased. Conclusion: Thanks to the usage of chromate-reduced cement, chromate sensitization continues to decline in the building trade. The increase of epoxy resin sensitization must prompt intensified prevention efforts. When recommending protective gloves, thiuram-free products should be preferred. The most important allergens are covered by the following test series recommended by the German Contact Dermatitis Research Group (DKG): DKG baseline series, DKG test series “building trade”, DKG rubber series.